PENGARUH IKLIM ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN OPERASIONAL PADA PTS X DI JAKARTA - Yustinus Yuniarto (Business Management Journal, 2017)
This research would conducted in the Operational employee at a X private university in Jakarta, partially have a significant variable between organizational climate with job satisfaction, meanwhile the development of a career with no job satisfaction have no significant variable. Key Words- Organizational Climate, Development of career, Job Satisfaction